Review of the role of alcohol in drowning associated with recreational aquatic activity. Issue 2 (5th April 2004) - Driscoll, T R; Harrison, J A; Steenkamp, M
Abstract : Objective and design: To assess the role of alcohol in drowning associated with recreational aquatic activity by reviewing the English language literature published up to October 2003. Results: Alcohol is widely used in association with recreational aquatic activity in the United States, but there is minimal information regarding the extent of use elsewhere. A priori and anecdotal evidence suggests that alcohol is an important risk factor for drowning associated with recreational aquatic activity. Specific studies provide good evidence supporting this, but the extent of increased risk associated with alcohol use, and the attributable risk due to alcohol use, is not well characterised. Drowning appears to be the overwhelming cause of death associated with recreational aquatic activity with alcohol detected in the blood in 30%–70% of persons who drown while involved in this activity. The few relevant studies on degree of increased risk suggest persons with a blood alcohol level of 0.10 g/100 ml have about 10 times the risk of death associated with recreational boating compared with persons who have not been drinking, but that even small amounts of alcohol can increase this risk. The population attributable risk seems to be in the range of about 10%–30%. Conclusions: Alcohol consumption significantly increases the likelihood of immersions resulting in drowning during aquatic activities. However, more information is required if appropriate prevention activities are to be planned, initiated, and evaluated. This includes better information on alcohol use, and attitudes to alcohol use, in association with recreational aquatic activity, and the nature and extent of increased risk associated with alcohol use. Evaluation of interventions is also needed.